O modelowaniu deformacyjnym. Maxa Webera koncepcja typów idealnych - Godek, Lidia (Człowiek i Społeczeństwo, 2016)
The article aims to reconstruct the idealization procedure understood as a deformational means of concept modelling in the theory proposed by Max Weber. The ideal type represents the basic form of the deformational transformation. Deformational modelling refers to a strategy of conscious and deliberate distortion of an object of empirical reality in varied and consequently counterfactual ways. The method essentially seeks to account for a concept by highlighting significant characteristics of the empirical content of investigated socioeconomic phenomena at the expense of their actual exemplification. The ideal type is a deformed means of representing a selected real-life phenomenon or object, oriented towards the fulfilment of specific cognitive goals while taking into account all methodological conditions involved in the process of its construction. By reference to Leszek Nowak’s concept of “cross of spiritual powers”, it is possible to determine the type of deformational modelling presented by the concept under discussion. Based on the analysis presented in the article, it was concluded that the ideal type represents quantitative deformation (positive potentialization).